Obesity, hypertension and diuretic use as risk factors for incident gout: a systematic review and meta-analysis of cohort studies - Peter L. Evans (Arthritis Research & Therapy, 2018)
Abstract Background Gout treatment remains suboptimal. Identifying populations at risk of developing gout may provide opportunities for prevention. Our aim was to assess the risk of incident gout associated with obesity, hypertension and diuretic use. Methods We conducted a systematic review and meta-analysis of prospective and retrospective cohort studies in adults (age ≥ 18 years) from primary care or the general population, exposed to obesity, hypertension or diuretic use and with incident gout as their outcome. Results A total of 9923 articles were identified: 14 met the inclusion criteria, 11 of which contained data suitable for pooling in the meta-analysis. Four articles were identified for obesity, 10 for hypertension and six for diuretic use, with four, nine and three articles included respectively for each meta-analysis. Gout was 2.24 times more likely to occur in individuals with body mass index ≥ 30 kg/m2 (adjusted relative risk 2.24 (95% confidence interval) 1.76–2.86). Hypertensive individuals were 1.64 (1.34–2.01) and 2.11 (1.64–2.72) times more likely to develop gout as normotensive individuals (adjusted hazard ratio and relative risk respectively). Diuretic use was associated with almost 2.5 times the risk of developing gout compared to no diuretic use (adjusted relative risk 2.39 (1.57–3.65)). Conclusions Obesity, hypertension and diuretic use are risk factors for incident gout, each more than doubling the risk compared to those without these risk factors. Patients with these risk factors should be recognised by clinicians as being at greater risk of developing gout and provided with appropriate management and treatment options.